2015
DOI: 10.3906/sag-1410-31
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence among women registered with a family health center in the Southeastern Anatolia Region and the factors affecting its prevalence

Abstract: Background/aim: In regions such as Şanlıurfa, Turkey, where the fertility rate is high, suitable health policies to easily and successfully treat urinary incontinence (UI) are needed. This study was conducted to determine the prevalence and risk factors for UI among women in the region. Materials and methods:The participants in this cross-sectional study were selected by using 30 cluster sampling methods. A total of 300 women in the age group of 15-49 years were contacted to participate. Results:The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…The prevalence of UI has been reported to range from 16% to 46% among women living in Turkey . The prevalence of UI in this study (37%) is consistent with the rates reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of UI has been reported to range from 16% to 46% among women living in Turkey . The prevalence of UI in this study (37%) is consistent with the rates reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…19 Moreover, it has been reported that rates of seeing a doctor are higher for women between 40 and 50 years of age with urgency UI. 19 A study performed in an eastern city in Turkey that has the highest fertility rate reported that the rate of visiting a doctor due to UI was 8%, 21 compared with a rate of 18.5% in another eastern city. 27 In a study conducted in Ankara, 43.5% of women with UI went to a physician.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies reported episiotomy data ( n = 46) and were set in medical facilities ( n = 69). Three studies reported combined results of births in medical facilities and in the community (Assarag et al 2013; Gözükara et al 2015; Iyengar 2012) and one study, by Koettker et al (2012), focus on planned home births with women with low risk pregnancies. Most studies’ population were healthy primiparous women with singleton pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of daily UI ranges from 5% to 15% for middle‐aged and older women 3,4 . Studies conducted in Turkey report that the prevalence of UI is 20.5% to 68.8% among women ages 15 and older 5‐7 . The most common types of UI are stress urinary incontinence (SUI), urge urinary incontinence (UUI), and mixed urinary incontinence (MUI) 8 .…”
Section: Introductionmentioning
confidence: 99%